A comparative study of ultrasonography versus peripheral nerve stimulator-guided obturator nerve block for transurethral resection of bladder tumor under spinal anesthesia - Sahu, Mandakini; Alok Pratap Singh; Kuldeep Kumar Patel (Asian Journal of Medical Sciences, 2024)
Background: Transurethral resection of bladder tumor (TURBT) is usually done spinal anesthesia but it does not prevent the obturator reflex leading to bladder perforation, bleeding, or incompletely resection of resection of the tumor which could be prevented by obturator nerve block (ONB) in TURBT. Aims and Objectives: The aim of our study is to compare the effectiveness of ONB by peripheral nerve stimulator (PNS) and ultrasonography (USG) in TURBT and also compare morbidity between USG- and PNS-guided ONB in TURBT under spinal anesthesia. Materials and Methods: Sixty patients were randomly divided into two groups. Group (1) patients had a PNS-guided ONB and Group (2) patients had ONB-guided ONB. The presence or absence of adductor muscles reflexes was recorded. Bladder perforation and bleeding during surgery were also recorded. Results: A success rate of 90% was achieved in the Group (2) compared to 66% in Group (1) which was clinically significant with P=0.049. Complete bladder perforation was detected in four patients in Group (1) whereas no perforation was observed in Group (2). Bleeding was observed in both groups but severe bleeding was present in five patients in Group (1) and required a blood transfusion. Conclusion: We concluded that USG-guided ONB is more efficient and safer as compared to PNS-guided ONB.